Relationships among inferiority feelings, fear of negative evaluation, and social anxiety in Chinese junior high school students - Li, Jiajian; Jia, Shuxin; Wang, Lishen; Zhang, Mingming; Chen, Shunsen (Frontiers in Psychology, 2023)
This study aimed to explore the relationship between a sense of inferiority and social anxiety in Chinese junior high school students. In addition, it examined the potential mediating effect of fear of negative evaluation in this relationship. Methods: A survey was administered to a sample of 850 Chinese junior high school students. The Feelings of Inadequacy Scale, Brief Fear of Negative Evaluation Scale, and Social Avoidance Distress Scale were used. Results: First, there were significant positive correlations between all subscales for the inferiority feelings, social anxiety, and fear of negative evaluation. Furthermore, fear of negative evaluation mediated the predictive effects of four inferiority subscales (i.e., self-esteem, academic ability, appearance, and physical ability) for social anxiety. However, the total score for the sense of inferiority and social confidence subscale lacked this mediating effect. Conclusion: The inferiority feelings of self-esteem, academic ability, appearance, and physical ability may directly and indirectly predict social anxiety through fear of negative evaluation.